PENERAPAN ALGORITMA BRUTE FORCE PADA MENU SEARCH WEBSITE "CALONKU" DALAM RANGKA PEMILU BERBASIS WEB - Yola Rahmawati; Irwan Adi Pribadi; Yunda Heningtyas (Jurnal Pepadun, 2021)
General elections are a means of people's involvement in the government process. Democratic countries, including Indonesia, conduct general elections. General election does not always go smoothly, at times tinged with some constraints. The lack of information has prompted a platform to contain the complete information that voters need. Website "Calonku" was created to meet the shortage of such information. In this study, the website "Calonku" implements the algorithm in its search feature, brute force deemed appropriate for solving problems using a straightforward approach. This research discusses the brute force algorithm's appropriate level and effectiveness on the "Calonku" system. Testing the brute force algorithm's performance is by calculating the recall, precision, and accuracy. This test calculates the similarity of each document to the given query. Similarity calculation will produce a weight on each paper that determines how relevant it is to the question. In this study, the average Accuracy value was 0.76 Recall of 0.85, and an average Precision of 0.83.